From Diplomacy to Industry: Evaluating the Long-Term Impacts of Indonesia – Türkiye Defense Cooperation on Regional Stability - Nurul Athirah (Journal of Migration and Political Studies)
Building on over seventy years of relations, Indonesia-Türkiye’s bilateral cooperation experienced significant growth following the 2010 defense agreement. The collaboration between Indonesia and Türkiye exemplifies a progressive method in defense diplomacy, integrating strategic cooperation with industrial innovations. Anchored in shared geopolitical interests, this collaboration has led to significant advancements, including the development of the Tiger Tank (KAPLAN MT/APC) and unmanned aerial vehicles (UAV), representing critical milestones in Indonesia's defense modernization and industrial self-reliance. This paper evaluates the long-term impacts of Indonesia-Türkiye defense collaboration on Southeast Asia’s regional stability and Indonesia’s defense industry growth. The findings reveal that this partnership provides strategic benefits for both nations. For Indonesia, it facilitates access to advanced defense technology, strengthening its domestic defense industry and reducing reliance on imports. For Türkiye, the partnership solidifies its position as a key defense supplier in Southeast Asia, expanding its geopolitical and economic influence. This study highlights the dual role of the Indonesia-Türkiye partnership in enhancing Indonesia’s defense capabilities and contributing to a resilient regional security architecture amid intensifying great power rivalries. Utilizing a descriptive qualitative methodology, the research draws on official documents, bilateral agreements, policy statements, academic literature, and media reports. The findings reveals that this collaboration advances Indonesia’s technological independence, strengthens its geopolitical positioning, and supports a more autonomous foreign policy. Amid a complex global geopolitical landscape, the partnership serves as a critical foundation for shared national interests and regional stability.